A functional Wood–Ljungdahl pathway devoid of a formate dehydrogenase in the gut acetogens Blautia wexlerae, Blautia luti and beyond. (11th May 2022) - Trischler, Raphael; Roth, Jennifer; Sorbara, Matthew T.; Schlegel, Xenia; Müller, Volker
Summary: Species of the genus Blautia are typical inhabitants of the human gut and considered as beneficial gut microbes. However, their role in the gut microbiome and their metabolic features are poorly understood. Blautia schinkii was described as an acetogenic bacterium, characterized by a functional Wood–Ljungdahl pathway (WLP) of acetogenesis from H2  + CO2 . Here we report that two relatives, Blautia luti and Blautia wexlerae do not grow on H2  + CO2 . Inspection of the genome sequence revealed all genes of the WLP except genes encoding a formate dehydrogenase and an electron‐bifurcating hydrogenase. Enzyme assays confirmed this prediction. Accordingly, resting cells neither converted H2  + CO2 nor H2  + HCOOH + CO2 to acetate. Carbon monoxide is an intermediate of the WLP and substrate for many acetogens. Blautia luti and B . wexlerae had an active CO dehydrogenase and resting cells performed acetogenesis from HCOOH + CO2  + CO, demonstrating a functional WLP. Bioinformatic analyses revealed that many Blautia strains as well as other gut acetogens lack formate dehydrogenases and hydrogenases. Thus, the use of formate instead of H2  + CO2 as an interspecies hydrogen and electron carrier seems to be more common in the gut microbiome.